Community adaptation strategies in Nairobi informal settlements: Lessons from Korogocho, Nairobi-Kenya - Christine Njuhi Muchiri; Romanus Otieno Opiyo (Frontiers in Sustainable Cities, 2022)
Informal settlements are often the hotspots of vulnerability as evidenced by the recurrent environmental and climate-related shocks and stressors. Despite this exposure and susceptibility, their role in spearheading disaster risk preparedness and response is often overlooked. This exploratory research profiles four local community initiatives for climate mitigation and adaptation within Korogocho informal settlement in Kenya. Findings from 10 purposefully sampled key informants and 30 stratified sampled residents across nine villages within the informal settlement demonstrated the impact of locally led initiatives in creating awareness and developing the absorptive, adaptive and transformative capacity of communities for climate resilience. The research findings elaborate on the outstanding performance of community derived initiatives, whilst putting emphasis on the need for active dialogue and collaboration between communities, policy makers and practitioners. Additionally, the climate agenda ought to be able to simultaneously promote environmental benefits and the socio-economic wellbeing of the people. This study accentuates the role of smart approaches to climate literacy based on existing community structures that leverage on local experiential knowledge. These include digital storytelling, comics, art, music, local radio stations, community opinion leaders and chief barazas. A key takeaway is the significant role of children in transformative climate resilience. This is facilitated by the fact that they may comprehend climate change implications better than adults augmenting the possibility of human behavioral change toward pro-environmental deeds1.